2012
DOI: 10.1364/josab.29.003271
|View full text |Cite
|
Sign up to set email alerts
|

Carrier-envelope phase shift of few-cycle pulses along the focus of lenses and mirrors beyond the nonreshaping pulse approximation: the effect of pulse chirp

Abstract: The carrier-envelope phase (CEP) shift of few-cycle pulses along a focal region is evaluated without neglecting the pulse reshaping inherent to any focusing process. The CEP shift is then found to strongly depend on the chirp of the focused pulse. Based on this effect, realistic optical systems for focusing few-cycle pulses are proposed to control their focal CEP shift for their phase-sensitive interactions with matter.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
22
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 15 publications
0
22
0
Order By: Relevance
“…The second contribution includes the effect of the small pulse reshaping, and depends on the pulse shape itself. For on-axis points only, it has been shown that any small amount of chirp in the focused pulse drastically alters the CEP map [20]. Here we evaluate the two contributions for off-axis points with chirped or unchirped Gaussian pulses, providing thus a complete description of the CEP map about the focus.…”
Section: The Three-dimensional Cep Mapmentioning
confidence: 99%
See 2 more Smart Citations
“…The second contribution includes the effect of the small pulse reshaping, and depends on the pulse shape itself. For on-axis points only, it has been shown that any small amount of chirp in the focused pulse drastically alters the CEP map [20]. Here we evaluate the two contributions for off-axis points with chirped or unchirped Gaussian pulses, providing thus a complete description of the CEP map about the focus.…”
Section: The Three-dimensional Cep Mapmentioning
confidence: 99%
“…Of particular interest is the situation in which the CEP is constant transversally and axially. Equating (20) and (21), this effect is seen to be possible in the focal region only with an input beam with g ≥ 1.15 at a certain position ζ in [−1, 1] (where the curves in FIG. 1(d) and FIG.…”
Section: A Design Of the Cep Map With Focusing Mirrorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Figure 1 illustrates the situation with the usual model with factorized field in space and time at the focus or waist z = 0, in which the Gaussian waist width s ω ≡ s is independent of frequency [16]. While for a few-cycle pulsed Gaussian beam (l = 0) the pulse shape on its maximum (at r = 0) is substantially unaltered [22,23], the same few-cycle pulse on the bright ring of a RPB widens and distorts, particularly for high |l|, as seen in Fig. 1.…”
mentioning
confidence: 99%
“…(24). For linearly polarized pulses, the term with a 0 0 ∕a 0 describes spectral filtering due to diffraction, and results in red-or blueshift of the carrier oscillations [12], or in reshaping of the real amplitude for chirped pulses [21]. These effects depend not only on the space-dependent filtering factor a 0 0 ∕a 0 but also on the temporal shape of the source pulse through dA x;y τ∕dτ∕A x;y , and are therefore generally different for the two components of the source pulse.…”
mentioning
confidence: 99%